SIMULATION OF ACID DRAINAGE FORMING AND PREDICTION OF WATER QUALITY IN PIT LAKE (CASE STUDY IN PT. ARUTMIN INDONESIA, ASAM-ASAM SITE). - Amin, Fitrani
Coal mining in Indonesia used to apply open pit mining system, Asam-Asam site by PT. Arutmin Indonesia, which is located in South Kalimantan Province is one of them. Backfilling that used to be applied in post-mining stage cannot be applied maximally because of lack of top soil. That phenomenon causing void in mining area that is called pit lake. Problem that can emerge from pit lake is water quality by rain water that fall into pit lake. The rain water leached rock wall and influenced by environment will impact the water quality in Asam-Asam site, PT. Arutmin Indonesia. Water quality prediction that will occur in pit lake will be simulated using PHREEQC computer application.Based on sample location in rock wall lithology scheme, scenario of water quality prediction will be arranged. Besides, current mining activity is considerably influence the scenario arrangement. Prediction value of pH from scenario A is 2,185 and scenario B is 3,012, which indicate the water quality in pit lake is acid, furthermore both are passing the acidity value limit. Sulphate (SO4) concentration in A scenario (1177,76 mg/L) is higher than B scenario (269,95 mg/L). Furthermore, the others water quality components such as Al and Fe concentration that are gained from prediction in A scenario are 36,675 mg/L and 1641,73 mg/L, then in B scenario are 0,160 mg/L for Al concentration and 10,027 mg/L for Fe concentration.